Magnesium Utilization in Dolomite Rocks by Struvite Precipitation in an Insulated Column Reactor - Edahwati, L; Sutiyono, S; Fauziyyah, Indah (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
Dolomite is a natural mineral rock with the chemical formula CaMg(CO3)2. Pure dolomite contains 21.70% calcium and 13.04% magnesium. Dolomite has not been widely used in the industrial sector until now. One way to increase the economic value of dolomite rock is to utilize its magnesium content as a precursor to struvite mineral which is the raw material for slow release fertilizer. Under alkaline conditions, struvite minerals are formed at concentrations of Mg2+, NH4+, and PO43-. Struvite solution (MAP) can be prepared by reacting phosphoric acid, ammonium hydroxide, and dolomite as a magnesium source in a molar ratio of 1:1:1. In a continuously operated isolated column reactor, the pH ranged from 8 to 12, and the reactor inlet air velocity ranged from 0.25 to 1.25 L/min. The chemical elements of dried struvite were determined using XRF (X-Ray Fluorescence), and the morphology was analyzed using SEM (Scanning Electron Microscope). At the same time, the crystal phase composition was identified using the Rietveld XRD (X-Ray Diffraction) technique. Based on the results of XRF analysis, the highest magnesium content was found under operating conditions with pH 12, air rate 0.75 L/min, and magnesium content 15.5%.